Giải phương trình:
\(2x-1=x\sqrt{x}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a.
\(3\sqrt{-x^2+x+6}\ge2\left(1-2x\right)\)
\(\Leftrightarrow\left[{}\begin{matrix}\left\{{}\begin{matrix}-x^2+x+6\ge0\\1-2x< 0\end{matrix}\right.\\\left\{{}\begin{matrix}1-2x\ge0\\9\left(-x^2+x+6\right)\ge4\left(1-2x\right)^2\end{matrix}\right.\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}\left\{{}\begin{matrix}-2\le x\le3\\x>\dfrac{1}{2}\end{matrix}\right.\\\left\{{}\begin{matrix}x\le\dfrac{1}{2}\\25\left(x^2-x-2\right)\le0\end{matrix}\right.\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}\dfrac{1}{2}< x\le3\\\left\{{}\begin{matrix}x\le\dfrac{1}{2}\\-1\le x\le2\end{matrix}\right.\end{matrix}\right.\)
\(\Rightarrow-1\le x\le3\)
b.
ĐKXĐ: \(x\ge0\)
\(\Leftrightarrow\sqrt{2x^2+8x+5}-4\sqrt{x}+\sqrt{2x^2-4x+5}-2\sqrt{x}=0\)
\(\Leftrightarrow\dfrac{2x^2+8x+5-16x}{\sqrt{2x^2+8x+5}+4\sqrt{x}}+\dfrac{2x^2-4x+5-4x}{\sqrt{2x^2-4x+5}+2\sqrt{x}}=0\)
\(\Leftrightarrow\dfrac{2x^2-8x+5}{\sqrt{2x^2+8x+5}+4\sqrt{x}}+\dfrac{2x^2-8x+5}{\sqrt{2x^2-4x+5}+2\sqrt{x}}=0\)
\(\Leftrightarrow\left(2x^2-8x+5\right)\left(\dfrac{1}{\sqrt{2x^2+8x+5}+4\sqrt{x}}+\dfrac{1}{\sqrt{2x^2-4x+5}+2\sqrt{x}}\right)=0\)
\(\Leftrightarrow2x^2-8x+5=0\)
\(\Leftrightarrow x=\dfrac{4\pm\sqrt{6}}{2}\)
Đặt \(\left\{{}\begin{matrix}\sqrt{x+3}=a\\\sqrt{x+1}=b\end{matrix}\right.\left(a,b\ge0\right)\)
\(PT\Leftrightarrow a+2xb-2x-ab=0\\ \Leftrightarrow2x\left(b-1\right)-a\left(b-1\right)=0\\ \Leftrightarrow\left(2x-a\right)\left(b-1\right)=0\\ \Leftrightarrow\left[{}\begin{matrix}2x=a\\b=1\end{matrix}\right.\)
Với \(2x=a\Leftrightarrow x+3=4x^2\left(x\ge0\right)\Leftrightarrow x=1\left(tm\right)\)
Với \(b=1\Leftrightarrow x+1=1\Leftrightarrow x=0\left(tm\right)\)
Vậy PT có nghiệm \(x\in\left\{0;1\right\}\)
a: ĐKXĐ: \(\left\{{}\begin{matrix}2x-3>=0\\x-1>0\end{matrix}\right.\)
=>\(\left\{{}\begin{matrix}x>=\dfrac{3}{2}\\x>1\end{matrix}\right.\Leftrightarrow x>=\dfrac{3}{2}\)
\(\dfrac{\sqrt{2x-3}}{\sqrt{x-1}}=2\)
=>\(\sqrt{\dfrac{2x-3}{x-1}}=2\)
=>\(\dfrac{2x-3}{x-1}=4\)
=>4(x-1)=2x-3
=>4x-4=2x-3
=>4x-2x=-3+4
=>2x=1
=>\(x=\dfrac{1}{2}\left(loại\right)\)
b: ĐKXĐ: 2x+15>=0
=>x>=-15/2
\(x+\sqrt{2x+15}=0\)
=>\(\sqrt{2x+5}=-x\)
=>\(\left\{{}\begin{matrix}-x>=0\\\left(-x\right)^2=2x+5\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}-\dfrac{15}{2}< =x< =0\\x^2-2x-5=0\end{matrix}\right.\)
=>\(\left\{{}\begin{matrix}-\dfrac{15}{2}< =x< =0\\\left(x-1\right)^2=6\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}-\dfrac{15}{2}< =x< =0\\\left[{}\begin{matrix}x-1=\sqrt{6}\\x-1=-\sqrt{6}\end{matrix}\right.\end{matrix}\right.\)
=>\(\left\{{}\begin{matrix}-\dfrac{15}{2}< =x< =0\\\left[{}\begin{matrix}x=\sqrt{6}+1\left(loại\right)\\x=-\sqrt{6}+1\left(nhận\right)\end{matrix}\right.\end{matrix}\right.\)
`\sqrt{x^2+2x+1}=\sqrt{x+1}`
Điều kiện:`x>=-1`
`pt<=>\sqrt{(x+1)^2}=\sqrt{x+1}`
`<=>\sqrt{x+1}(\sqrt{x+1}-1)=0`
`+)\sqrt{x+1}=0<=>x=-1`
`+)\sqrt{x+1}=1<=>x=0`
Vậy `S={0,-1}`